Self compassion dan subjective well being pada mahasiswa dengan orang tua tunggal - Ananda, Moch. Rizky; Efendy, Mamang; Rista, Karolin (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
Abstract Subjective well being is one of the important factors in students with single parent because it is related to getting happiness and avoiding pain. This study aims to determine whether there is a relationship between self compassion and subjective well being in students with single parent. Quantitative research method with the number of respondents as many as 115 students with single parent who were taken with snowball sampling technique. The research scale uses a self compassion scale developed by the researcher and uses a subjective well being scale. Data analysis techniques using product moment correlation analysis. The results showed a positive and significant relationship between self compassion and subjective well being in students with single parent. Self compassion helps increase positive feelings and reduce negative feelings felt to achieve subjective well being in students with single parent. Abstrak Subjective well being merupakan salah satu faktor penting pada mahasiswa dengan orang tua tunggal karena berhubungan dengan mendapatkan kebahagiaan dan menghindari rasa sakit. Penelitian ini bertujuan untuk mengetahui apakah ada hubungan self compassion dengan subjective well being pada mahasiswa dengan orangtua tunggal. Metode penelitian kuantitatif dengan jumlah responden sebanyak 115 mahasiswa dengan orangtua tunggal yang diambil dengan teknik snowball sampling. Skala penelitian menggunakan skala self compassion yang dikembangkan sendiri oleh peneliti dan menggunakan skala subjective well being. Teknik analisis data menggunakan analisis korelasi product moment. Hasil penelitian menunjukkan adanya hubungan positif dan signifikan antara self compassion dengan subjective well being pada mahasiswa dengan orangtua tunggal. Self compassion membantu meningkatkan perasaan positif dan menurunkan perasaan negatif yang dirasakan untuk mencapai subjective well being pada mahasiswa dengan orangtua tunggal.